Function of copulatory plugs in house mice: mating behavior and paternity outcomes of rival males - Sutter, Andreas; Simmons, Leigh W.; Lindholm, Anna K.; Firman, Renée C. (Behavioral ecology, 2016)
Lay Summary Mating plugs increase a males' paternity share in competition against rival males. In many animals, males plug the female reproductive tract after mating, supposedly to prevent females from remating. We show that male mice are strongly limited in plug-producing ejaculate components. Variation in plug size did not predict female remating, but influenced competing males' competitive fertilization success when remating occurred.Polyandry is widespread across animal taxa and subjects males to intense postcopulatory sexual selection which favors adaptations that enhance a male's paternity success, either by decreasing the risk of sperm competition and/or by increasing the competitiveness of the ejaculate. Copulatory plugs deposited by males are thought to have evolved in the context of sperm competition. However, experimental studies that assess the function of copulatory plugs remain scarce. Moreover, most studies have used unnatural manipulations, such as ablating plug-producing male glands or interrupting copulations. Here, we investigated whether repeated ejaculation affects plug size in a mammalian model species, the house mouse. When males experience short periods of sexual rest we found that plug size decreased over repeated ejaculations so that time since last ejaculation can be applied as an approximation for plug size. We induced natural variation in plug size arising from variation in male sexual restedness and investigated the behavior and paternity success of rival males. Male behavior in the offensive mating role (second) was influenced, albeit not significantly, by the sexual restedness of the first male to mate, and therefore the size of his plug. However, second males sired a significantly greater proportion of embryos when competing against a male that had recently mated compared with a male that had not. This supports a potential role of the plug in promoting a male's competitive fertilization success when remating occurs, which could be mediated both by delaying female remating and by ensuring efficient sperm transport through the female reproductive tract.